Managing a transport company to enter new markets: case of Kazakhstani transportation industry - Akhmetzhanova, A.Kh.; Smagulova, N.T.; Beysekova, Zh.I.; Maulina, N.H.; Musabekova, K.Zh. (BUKETOV BUSINESS REVIEW, 2024)
Object: The purpose of this study is to examine the efficiency management of transport companies in the Republic of Kazakhstan by analyzing key factors such as oil prices, passenger turnover, exchange rates, GDP, investments and export trends. Methods: Quantitative analysis is used using data from 2014 to 2023 to evaluate the effect of these parameters on the volume index (PVI) of the transport industry. Multiple linear regression modeling is performed to analyze the relationships between variables and the PMI index. Findings: Regression analysis shows a considerable positive relationship between oil prices and the PVI index, which indicates the impact of fluctuations in oil prices on the performance of the transport sector. In addition, passenger turnover demonstrates a significant negative relationship with the PVI index, which highlights potential problems in optimizing passenger transportation systems. However, variables such as exchange rates, GDP, investments, and export trends did not show statistical significance in the regression model. Conclusions: Efficient management of transportation companies in Kazakhstan needs to take into account various internal and external factors. Strategies to address the effects of oil price fluctuations, optimize passenger transportation systems, manage currency risks, exploit economic growth opportunities and explore export potential are essential to increase productivity and ensure the sustainability of the transport sector.